Essential neuropharmacology : the prescriber's guide - Silberstein, Stephen D.; Marmura, Michael James; Stahl, Stephen M., 1951- (Cambridge : Cambridge University Press, 2010)
'Essential Neuropharmacology: The Prescriber's Guide expertly reviews the most important medications used by neurologists in their practice. Experienced clinicians share their expert knowledge about the best use of medications in patient care. Each drug listing contains the range of indications, their advantages and disadvantages, and tips for dosing and avoiding adverse effects. Experts in fields such as multiple sclerosis, movement disorders, neuromuscular disorders, epilepsy, stroke, pain and headache summarize how neurologists use these medications to their best effect, and discuss off-label uses in neurology. Evidence is taken from recent clinical trials, which helps the reader relate the content to everyday clinical practice. The detailed descriptions of each medication enable the user to make quick and informed decisions with the confidence they need to best serve the clinical needs of their patients. This book is an essential, user-friendly reference suitable for all neurologists at all stages of their careers'--Provided by publisher.
Acetozolamide -- Almotriptan -- Alteplase -- Amantadine -- Amitriptyline -- Apomorphine -- Armodafinil -- Aspirine (acetylsalicylic acid) -- Azathioprine -- Baclofen -- Benztropine -- Botulinum Toxin A -- Botulinum Toxin B -- Bromocriptine -- Carbamezapine -- Carbidopa/Levidopa -- Carisoprodol -- Chlorpromazine -- Clonazepam -- Clonidine -- Clopidogrel -- Clozapine -- Cyclobenzaprine -- Cyclophosphamide -- Cyclosporine -- Cyproheptadine -- Dantrolene -- 3,4 diaminopyrimidine -- Diazepam -- Dihydroergotamine -- Dipyridamole and aspirin -- Donepezil -- Droperidol -- Duloxetine -- Edrophonium -- Eletriptan -- Entacapone -- Ethosuximide -- Felbamate -- Flunarizine -- Fluoxetine -- Frovatriptan -- Gabapentin -- Galantamine -- Glatiramer acetate -- Guanfacine -- Guanidine hydrochloride -- Haloperidol -- Heparin -- Immune globulin intravenous (IGIV) -- Indomethacin -- Interferon-beta -- Lacosamide -- Lamotrigine -- Levetiracetam -- Lithium -- Mannitol -- Meclizine -- Memantine -- Metaxalone -- Methocarbamol -- Methotrexate -- Methylergonovine -- Methysergide -- Metoclopramide -- Mexiletine -- Mitoxantrone -- Modafinil -- Mycophenolate mofetil -- Naratriptan -- Natalizumab -- Nimodipine -- Nortriptyline -- Oxcarbazepine -- Penicilamine -- Phenobarbital -- Phenytoin -- Pizotifen -- Pramipexole -- Prednisone -- Pregabalin -- Primidone -- Prochlorperazine -- Propranolol -- Pyridostigmine -- Quetiapine -- Quinine sulfate -- Rasagiline -- Reserpine -- Riluzole -- Rituximab -- Rivastigmine -- Rizatriptan -- Ropinirole -- Rufinamide -- Selegiline -- Sumatriptan -- Tetrabenazine -- Tiagabine -- Timolol -- Tizanidine -- Topiramate -- Trientine hydrochloride -- Trihexyphenidyl -- Valproic acid -- Venlafaxine -- Verapamil -- Vigabatrin -- Warfarin -- Zolmitriptan -- Zonisamide.
Keywords: Central Nervous System Agents -- pharmacology -- Handbooks; Central Nervous System Agents -- therapeutic use -- Handbooks; Central Nervous System Diseases -- drug therapy -- Handbooks; Neuropharmacology; Handbooks, manuals, etc